Integrating the Ken-duren tradition of Wonosalam into ethno-STEM based biodiversity module to improve students’ science literacy - Rizki Yudha Sentika; Wisanti Wisanti; Pramita Yakub (EDUSAINS, 2025)
This study aims to develop and evaluate the effectiveness of an Ethno-STEM-based biodiversity module integrated with the Ken-Duren Wonosalam tradition in improving the scientific literacy of tenth-grade high school students, employing a Research and Development (R&D) approach. The study follows the 4D model (Define, Design, Develop, Disseminate). The subjects were 15 tenth-grade students of Darul Ulum 1 Unggulan Jombang High School. Data was collected through three expert validations, consisting of one material expert, one media expert, and one education expert who evaluated the feasibility of the developed module. The validation results by two material experts and one media expert showed an average value of 3.79 with a "valid" category. The practicality test showed that the module was easy to use and implement in learning. The effectiveness test using the paired sample t-test produced a p-value <0.05 which indicated a significant difference between students' pretest and posttest results. The results indicate that the Ethno-STEM-based biodiversity module is associated with improved students’ scientific literacy, as reflected in the pretest–posttest gains. However, because the study employed a one-group pretest–posttest design, the findings should be interpreted cautiously. The integration of the Ken-Duren local tradition appears to support more contextual and meaningful learning, highlighting its potential contribution to science education.